(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Phraseological units can play crucial role as component of any language by reflecting its cultural and historical background. This study analyzes phraseological units in the structural form and semantic features in order to emphasize their important role in communication. Due to usage of a comparative linguistic approach, we examine their utilize in a variety of contexts and the challenges they cause for translation. The study contributes to a deeper understanding of phraseology and opens their types by giving examples from “Tushda kechgan umrlar” by O’tkir Hoshimov.